Café Lifestyle And Identity Among Young Coffee Consumers In Makassar - Windarsari, Wiwin Riski (Abadi Institute, 2025)
In contemporary Makassar, café culture has become a powerful site of youth identity construction, cultural negotiation, and social aspiration. This study explores how coffee consumption among young people aged 18–30 transcends lifestyle trends to become a medium for performing modernity, asserting cultural roots, and navigating socioeconomic and spatial hierarchies. This research investigates the meanings and experiences embedded in café rituals across diverse social and economic contexts using a phenomenological qualitative approach including semi-structured interviews, participant observation, and digital diaries. Findings reveal that cafés function as identity laboratories where youth strategically curate hybrid selves, blending global coffee aesthetics with local philosophies such as Siri’ Na Pacce and Pappaseng. The study highlights how class and income shape café participation, with phenomena like “menu anxiety” reinforcing symbolic exclusions. It also uncovers new dimensions, including emotional self-regulation through café rituals, gendered expectations of visibility, and the digital extension of café experiences via social media as forms of aspirational performance. Contrary to the universalist “third place” theory, cafés in Makassar operate as contested cultural arenas, simultaneously enabling self-expression and reinforcing structural boundaries. This research advances a decolonial framework for understanding youth consumption in the Global South by centering Eastern Indonesian epistemologies. It calls for inclusive urban strategies that recognize cafés not just as commercial spaces, but as everyday theaters of cultural resistance, belonging, and meaning-making.